A Two-Moment Bulk Microphysics Coupled with a Mesoscale Model WRF：Model Description and First Results - 高文华 赵凤生 胡志晋 冯绚 (Advances in atmospheric sciences, 2011)
The Chinese Academy of Meteorological Sciences （CAMS） two-moment bulk microphysics scheme was adopted in this study to investigate the representation of cloud and precipitation processes under different environmental conditions.The scheme predicts the mixing ratio of water vapor as well as the mixing ratios and number concentrations of cloud droplets,rain,ice,snow,and graupel.A new parameterization approach to simulate heterogeneous droplet activation was developed in this scheme.Furthermore,the improved CAMS scheme was coupled with the Weather Research and Forecasting model （WRF v3.1）,which made it possible to simulate the microphysics of clouds and precipitation as well as the cloud-aerosol interactions in selected atmospheric condition.The rain event occurring on 27-28 December 2008 in eastern China was simulated using the CAMS scheme and three sophisticated microphysics schemes in the WRF model.Results showed that the simulated 36-h accumulated precipitations were generally agreed with observation data,and the CAMS scheme performed well in the southern area of the nested domain.The radar reflectivity,the averaged precipitation intensity,and the hydrometeor mixing ratios simulated by the CAMS scheme were generally consistent with those from other microphysics schemes.The hydrometeor number concentrations simulated by the CAMS scheme were also close to the experiential values in stratus clouds.The model results suggest that the CAMS scheme performs reasonably well in describing the microphysics of clouds and precipitation in the mesoscale WRF model.